A checklist of species of Podophryidae (Ciliophora: Suctoria) as Epibionts of Crustaceans - Ramírez-Ballesteros, Mireya; Mayén-Estrada, Rosaura (Zootaxa, 2022)
The epibiotic relationship between crustaceans and ciliates is frequent, for example, with species of suctorians. This work aims to present an updated list of species of the family Podophryidae worldwide distributed as epibionts of crustaceans and its geographic distribution. The available literature was checked, and all the species were verified. We found four species and four species indeterminata attached to 16 species of crustaceans. For the American continent, we obtained four species, and for Africa and Oceania, we did not find any species.